Odpowiedzi

2010-03-23T09:26:18+01:00
F(x)=(m-4)x"-3mx+1/2m.
F(x)=(8-4)x"-3*8x+1/2*8
f(x)=8x"-4x"-24x+4
f(x)=4x"-24x+4

∆=b"-4ac
∆=(-24)"-4*4*4
∆=576-64
∆=512
√∆=16√2


-b+√∆ 24+16√2 8(3+2√2)
x1=------- =------=------------------- =3+2√2
2a 2*4 8


-b-√∆ 24-16√2 8(3-2√2)
x2=------- =------=------------------- =3-2√2
2a 2*4 8

1 5 1
2010-03-23T09:36:56+01:00
F(x)=(8-4)x"+3 *8x+1/2 *8
f(x)=4x" +24x+4
a=4----- b=24 ------c=4
delta= b "-4ac
delta=576-384
delta =192
pierw z delty=8 pierw z 3
x '=(-b+pierw z delty):2a
x'=(-24 +8 pier z3):2 *4
x'=-3 +pierw z 3

x"=(-b-pierw z delty):2a
x"=(-24-8pierw z3):2 *4
x"=-3-pierw z 3
1 5 1